Analisis Perencanaan dan Pengendalian Produksi untuk Meningkatkan Kelancaran Produksi OBH di PT XYZ - Riski Rosadi; Asep Kurniawan (Universitas Batanghari Jambi, 2026)
This study aims to analyze production planning and control to improve the smoothness of black cough syrup (OBH) production at PT XYZ. The company faces several challenges in its production process, such as raw material delays, sudden changes in market demand, and discrepancies between planning and production realization. This research employs a descriptive-qualitative approach using observation, interviews, and document analysis. Analytical tools include a process flowchart, Pareto chart, and fishbone (Ishikawa) diagram. The results reveal that inefficiencies in production are mainly caused by five core elements: human (errors and lack of training), machine (frequent breakdowns and limited capacity), method (inflexible planning), material (delayed supply), and environment (poor interdepartmental coordination). These findings are supported by in-depth interviews, indicating that production delays often stem from miscommunication between the planning and production execution teams. The practical implication of this study is the need for a more responsive PPC system and the digitalization of processes to enhance integration among departments. This research contributes to the development of production control strategies in the pharmaceutical industry, particularly in optimizing production flow. The findings are expected to serve as a foundation for managerial decision-making to strengthen adaptive and efficient production systems.